Ranking Index Berita New Normal dengan Metode Information Retrieval Menggunakan Vector Space Model - Nandang Suwela (Universitas Indraprasta PGRI Jakarta, 2020)
After three months of large scale social distancing major (PSBB), Indonesia is getting ready to enter a new order or commonly known as new normal, a new thing that many countries including Indonesia are forced to deal with. The new normal has become a rather interesting thing to discuss that many people are browsing for news orbiting around such topic regarding of what it is, how it is done and when exactly it’s implemented. The initial of this research is to calculate the accuracy of news browsing by computing the score rank so that the keywords that we use can acquire the results as we wanted. This research is using an experiment method in which gathering the news in the virtual world. .One of the ways to acquire the right documents is to make a ranking. Ranking is one of the branches from Information Retrieval System and one of the models that we can use to deal with such problem is the Vector Space Model. The dataset that we use is the Corona-related news through tokenizing, filtering, and stemming on preprocessing. The research results in proving that Vector Space Model (VSM) can be used and can help finding and computing the score rank of the news.